Pengembangan dan Pemberdayaan UMKM Kota Depok Di Masa Pandemi COVID-19 - Widyastuti, Tri; Parianom, Raden (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have a very large contribution to the nation's economic condition. The current economic situation affected by the Covid-19 pandemic has almost affected all business sectors, especially the MSME sector. The problems faced by business actors are mainly in terms of marketing or marketing which usually relies on direct sales. Utilization of information technology is expected to be a solution in solving sales, marketing and financial transaction problems of MSME actors. Information technology turned out to be a new thing and very difficult for market traders or business actors. IT-based behavior change for both buyers and sellers requires training and assistance in the areas of sales, marketing and financial transactions. The problem faced by partners today is that partners do not master digital marketing, digital sales and digital financial transactions. The solutions offered are training and assistance in digital marketing, sales and financial transactions.